1963
DOI: 10.1139/b63-100
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rates of Cladonia Alpestris, C. Mitis, and C. Rangiferina in the Taltson River Region, N.W.T.

Abstract: Data on the growth rate of lichens are essential to the understanding of the carrying capacities of rangelands used by caribou and reindeer in Canada. Recent Russian literature suggests fruticose lichens have three growth stages. The first stage is one of podetium accumulation. During the second stage, accumulation rate and decomposition rate are similar, while, in the third stage, decomposition of the Podetium is more rapid than accumulation. In the Taltson River region, the average annual linear growth rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
3

Year Published

1965
1965
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 0 publications
2
18
3
Order By: Relevance
“…Overall, it can be reasonably expected that time since the last disturbance will have a positive effect on the probability of lichen establishment and growth in a site. The association between C. stellaris and late successional forests [51,52] has previously been explained by the low growth rate of this species compared with the other caribou lichen species studied [53]. However, as den Herder et al [54] found in Finland, higher growth rates for C stellaris compared with C. mitis and C. rangiferina were previously found in our study area, including in dense forest stands where the abundance of C. stellaris is naturally relatively low [55].…”
Section: Discussionsupporting
confidence: 58%
“…Overall, it can be reasonably expected that time since the last disturbance will have a positive effect on the probability of lichen establishment and growth in a site. The association between C. stellaris and late successional forests [51,52] has previously been explained by the low growth rate of this species compared with the other caribou lichen species studied [53]. However, as den Herder et al [54] found in Finland, higher growth rates for C stellaris compared with C. mitis and C. rangiferina were previously found in our study area, including in dense forest stands where the abundance of C. stellaris is naturally relatively low [55].…”
Section: Discussionsupporting
confidence: 58%
“…One of the oldest ways is to measure the height increase of lichens by dividing the height of the podetium by the number of joints on the podetium (Igoshina, 1939;Andreyev, 1954;Scotter, 1963). Using this method, researchers have estimated the growth rate of individual lichens as 2.0 -4.0 mm/yr (Igoshina, 1939), 2.5 -6.0 mm/yr (Scotter, 1963), and 2.8 -5.1 mm/ yr (Skuncke, 1969). This method has been criticized (Kärenlampi, 1970) because it is not useful in an overgrazed area, and it does not allow separate measurements of growth rate for lichens of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increments between 2003 and 2005 provide indications that lichen fragments did establish, although it was not possible to confirm this with any certainty. Possible shrinkage of the thalli caused by drying (Scotter 1963) on some measurement occasions was not taken into account, and this could have influenced the cover estimates, but only weakly since the inventories were carried out at the same period of the year, and under similar climatic conditions, i.e. on overcast days, on every occasion.…”
Section: Lichen Establishment After Artificial Dispersalmentioning
confidence: 99%
“…The growth rate of reindeer lichens is generally low (Kärenlampi 1971, Helle et al 1983, den Herder et al 2003, as is their branching, which is assumed to be an annual event (Scotter 1963). The first natural colonizers of bare soil in boreal regions are crustose lichens and bryophyte species, followed by cup lichens (Cladonia spp.…”
Section: Introductionmentioning
confidence: 99%